2019
DOI: 10.1111/gbi.12359
|View full text |Cite
|
Sign up to set email alerts
|

Global marine redox changes drove the rise and fall of the Ediacara biota

Abstract: The role of O2 in the evolution of early animals, as represented by some members of the Ediacara biota, has been heavily debated because current geochemical evidence paints a conflicting picture regarding global marine O2 levels during key intervals of the rise and fall of the Ediacara biota. Fossil evidence indicates that the diversification the Ediacara biota occurred during or shortly after the Ediacaran Shuram negative C‐isotope Excursion (SE), which is often interpreted to reflect ocean oxygenation. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 91 publications
(288 reference statements)
8
85
1
Order By: Relevance
“…Despite the inability to use Tl isotopes to directly constrain ocean oxygenation, our interpretation of increased ocean oxygenation at the EN3a to EN3b transition is consistent with previously reported evidence for an oxygenation event during this time, which was based on globally enhanced continental weathering (Li et al, ; Sawaki et al, ), elevated marine sulfate concentrations and decreased sulfur isotope composition (Fike et al, ; Kaufman et al, ; Li et al, ; Loyd et al, ; Osburn et al, ), elevated marine iodate concentrations observed in a range of global depositional settings (Hardisty et al, ), and a positive U isotope excursion (Kendall et al, ; Zhang et al, ). Although spatially heterogeneous, paired δ 13 C and δ 34 S records show coincident negative excursions interpreted to represent an event that oxidized large dissolved organic carbon and sulfide pools in the deep oceans (Fike et al, ; Kaufman et al, ; Li et al, ; Loyd et al, ; Osburn et al, ; Shi et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Despite the inability to use Tl isotopes to directly constrain ocean oxygenation, our interpretation of increased ocean oxygenation at the EN3a to EN3b transition is consistent with previously reported evidence for an oxygenation event during this time, which was based on globally enhanced continental weathering (Li et al, ; Sawaki et al, ), elevated marine sulfate concentrations and decreased sulfur isotope composition (Fike et al, ; Kaufman et al, ; Li et al, ; Loyd et al, ; Osburn et al, ), elevated marine iodate concentrations observed in a range of global depositional settings (Hardisty et al, ), and a positive U isotope excursion (Kendall et al, ; Zhang et al, ). Although spatially heterogeneous, paired δ 13 C and δ 34 S records show coincident negative excursions interpreted to represent an event that oxidized large dissolved organic carbon and sulfide pools in the deep oceans (Fike et al, ; Kaufman et al, ; Li et al, ; Loyd et al, ; Osburn et al, ; Shi et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…The latter mechanism would be similar to the interpretation for the Phanerozoic events where the Tl isotope composition of seawater was observed to respond prior to the carbon isotope excursion (Ostrander et al, ; Them et al, ; Bowman et al, ; and reviewed in Owens, ). The decreasing U isotope (δ 235 U) composition of seawater recorded by shales from the Member IV of the Doushantuo Formation and carbonate from the Nama Group suggested a rapid and dramatic anoxic expansion from ~560–550 Ma (Kendall et al, ; Tostevin et al, ; Zhang et al, ), providing additional evidence for our proposed decrease in ocean oxygenation during the EN3c.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These global and local datasets are not necessarily in conflict, as the uranium proxy data may record an integrated global increase in the spatial extent of productive mid-depth waters at ~547 Ma. In fact, recent compilations of δ 238 U carb from globally distributed late (2020) 10:2240 | https://doi.org/10.1038/s41598-020-59335-2 www.nature.com/scientificreports www.nature.com/scientificreports/ Ediacaran successions do suggest a trend towards an increasingly oxygenated global ocean between 545-540 Ma, in the wake of the highly negative values recorded in the lower Nama Group and Dengying Formation [62][63][64] . However, these global oxygenation events were transient, and their influence on the pace of animal evolution in shallow shelf ecosystems which were subject to highly heterogeneous local redox conditions demands further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between 1% and 0.1% PAL is critical for metazoans (across this range of oxygen levels in modern OMZs there is a shift from low‐diversity animal assemblages to no animals), but this difference is within error of all reports of “low” mid‐Proterozoic atmospheric oxygen (e.g., Planavsky, Cole, et al, ). Further, most marine elemental or isotopic redox proxies calculate the proportion of anoxic or euxinic seafloor with considerable uncertainty (for instance, a recent U isotope study by Zhang et al, , estimated anoxic seafloor area prior to the Shuram carbon isotope excursion to be between 25% and 100%—an enormous range). Even if these proxies had less error they would not provide a full view of the water column redox landscape.…”
Section: Point–counterpoint Argumentsmentioning
confidence: 99%